KEMAMPUAN BERBAHASA ANAK DENGAN MEDIA CERITA BERGAMBAR - Yatiningsih; Fu’ad Arif Noor (QURROTI, 2020)
This research is to find out how to improve language skills using pictorial story media in BA 'Aisyiyah Gani Socokangsi Jatinom Klaten children. This research uses a type of classroom action research (PTK). The subjects of this study were children of group A BA 'Aisyiyah Gani Socokangsi Jatinom, Klaten, which consisted of 12 boys and 8 girls. The data collection techniques used were interviews, observation, and documentation. While the research instruments used were interview guidelines and observation sheets. The results of this study indicate that: 1) the use of pictorial story media is carried out in several steps, namely: a) preparing materials or learning materials to be delivered, b) conditioning students to be calm and paying attention, c) showing book covers while providing initial stimulation to the children then the teacher begins to read the story entitled "The Story of Uli and Bat", d) the teacher begins to ask questions to the child about the content of the story and concludes the story with the children, e) create a conducive, fun and enjoyable atmosphere, f) motivating students to carry out activities by giving gifts or rewards, 2) increasing language skills in early childhood at BA 'Aisyiyah Gani Socokangsi Jatinom Klaten after using pictorial story media which was originally only 25% increased in cycle I to 55% and in Cycle II reaches 90%. So the increase is 65%.